High frequency signal injection method for sensorless permanent magnet synchronous motor drives - Tan Jiunn Lin; Jurifa Mat Lazi; Zulkifilie Ibrahim; Md Hairul Nizam Talib; Azrita Alias; Ahmad Shukri Abu Hasim (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
The objective of this project is to design a high frequency signal injection method for sensorless control of permanent magnet synchronous motor (PMSM) drives. Generally, the PMSM drives control requires the appearance of speed and positon sensor to measure the motor speed hence to feedback the information for variable speed drives operation. The usage of the sensor will increase the size, cost, extra hardwire and feedback devices. Therefore, there is motivation to eliminate this type of sensor by injecting high frequency signal and utilizing the electrical parameter from the motor so that the speed and positon of rotor can be estimated. The proposed position and speed sensorless control method using high frequency signal injection together with all the power electronic circuit are modelled using Simulink. PMSM sensorless driveis simulated and the results are analyzed in terms of speed, torque and stator current response without load disturbance but under the specification of varying speed, forward to reverse operation, reverse to forward operation and step change in reference speed. The results show that the signal injection method performs well during start-up and low speed operation.